2015
DOI: 10.1371/journal.pone.0136592
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure Increases Monocyte Adhesion to the Vascular Endothelium, a Pro-Atherogenic Mechanism

Abstract: Epidemiological studies have shown that arsenic exposure increases atherosclerosis, but the mechanisms underlying this relationship are unknown. Monocytes, macrophages and platelets play an important role in the initiation of atherosclerosis. Circulating monocytes and macrophages bind to the activated vascular endothelium and migrate into the sub-endothelium, where they become lipid-laden foam cells. This process can be facilitated by platelets, which favour monocyte recruitment to the lesion. Thus, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…In our study, it has been observed that the levels of HB, RBC, PLT, NEU, and LYM are decreased signi cantly with a marked increase in the HCT, WBC, MON and reticulocyte count in rats exposed to arsenic compared to the control group. The results are consistent with some studies (Kajiguchi et al, 2005; Bhattacharya and Haldar, 2012; Sumedha and Miltonprabu, 2013; Lemaire et al, 2015;Ghosh et al, 2017;Su et al, 2018). This effect of Arsenic exposure on the hematopoietic system may be attributed to the mechanisms of arsenic toxicity which may induce hemolysis and erythrophagocytosis through increased oxidation of sulfhydryl groups in hemoglobin and decreased oxygen intake by cells as a result of decreased intracellular glutathione, which decreases the lifespan of erythrocytes (Abdul et al, 2015).…”
Section: Complete Blood Count (Cbc)supporting
confidence: 87%
“…In our study, it has been observed that the levels of HB, RBC, PLT, NEU, and LYM are decreased signi cantly with a marked increase in the HCT, WBC, MON and reticulocyte count in rats exposed to arsenic compared to the control group. The results are consistent with some studies (Kajiguchi et al, 2005; Bhattacharya and Haldar, 2012; Sumedha and Miltonprabu, 2013; Lemaire et al, 2015;Ghosh et al, 2017;Su et al, 2018). This effect of Arsenic exposure on the hematopoietic system may be attributed to the mechanisms of arsenic toxicity which may induce hemolysis and erythrophagocytosis through increased oxidation of sulfhydryl groups in hemoglobin and decreased oxygen intake by cells as a result of decreased intracellular glutathione, which decreases the lifespan of erythrocytes (Abdul et al, 2015).…”
Section: Complete Blood Count (Cbc)supporting
confidence: 87%
“…24,25 Adhesion molecules allow mononuclear cells to attach to the endothelium, a key step in atherosclerotic initiation. In experimental studies, As elevates circulating vascular inflammatory marker levels, including ICAM1 and VCAM1 2628 , increases monocyte adhesion to the vascular endothelium via increased binding to VCAM1 28 and increases atherosclerotic lesion formation, along with expression of inflammatory mediators, such as monocyte chemoattractant protein 1 (MCP1), at vascular lesion sites. 29 Levels of these circulating markers may predict future cardiovascular disease risk 3033 and of these, soluble VCAM1 and ICAM1 have been consistently related to chronic As exposure in studies among adults in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies carried out in various countries demonstrate that arsenic significantly increases the risk of atherosclerosis [55,56]. Several mechanisms may contribute to the development of atherosclerosis, including general pro-inflammatory cytokine secretion [10], increased ROS production [8], enhanced monocyte adhesion to vascular endothelium [57] and reduced cholesterol efflux from macrophages [7]. In murine models, at least, methylated metabolites and arsenic-3-methyltransferase play major roles in these proatherogenic effects of arsenic [58].…”
Section: Contribution To Diseases Associated With Chronic Environmentmentioning
confidence: 99%